Political Ecology in Transition in the Global South: Examining the Interplay of Environment, State, and Society in Colonial India (1800-1947) (Global Journal of Cultural Studies, 2024)
This paper presents an analysis of how historical transitions occurred, emphasising human actions and their interactions with the natural world, geography, climate, and the planet Earth. Anthropogenic actions have influenced changes in ecology and the environment throughout history. This impact intensified since the Industrial Revolution in England during the nineteenth century, spreading across the globe through the colonial and imperial pursuits of Western European nations. The paper adopts a methodological framework for understanding how historical transitions unfolded within the realm of political ecology in the Global South, drawing examples from colonial India under British rule. British colonial rule and its politically and economically driven ideologies drastically affected India’s natural environment, including its flora and fauna. This led to a reduction in ecological biodiversity from the latter part of the nineteenth century until the end of their rule in 1947. By employing transition theory as the primary method of historical investigation, this study aims to illustrate how the colonial state and its ideologues and officials influenced the Indian environment and society and how the transition framework can inform significant ecological changes in the Indian subcontinent during the nineteenth and early twentieth centuries.